The art of data analysis : how to answer almost any question using basic statistics - Jarman, Kristin H. (Hoboken, New Jersey : John Wiley & Sons, 2013)
'With an emphasis on critical thinking, The Art of Data Analysis: How to Answer Almost Any Question Using Basic Statistics presents fun and unique examples, guides readers through the entire data collection and analysis process, and introduces basic statistical concepts along the way. Leaving proofs and complicated mathematics behind, the author portrays the more engaging side of statistics and emphasizes its role as a problem-solving tool. In addition, light-hearted case studies illustrate the application of statistics to real data analyses, highlighting the strengths and weaknesses of commonly used techniques. Written for the growing academic and industrial population that uses statistics in everyday life, The Art of Data Analysis: How to Answer Almost Any Question Using Basic Statistics highlights important issues that often arise when collecting and sifting through data.'--Publisher's website.
The Basics. Statistics: The Life of the Party -- Lions, and Tigers, and ... Bigfoot? Oh, My: How Questionable Data Can Screw Up an Otherwise Perfectly Good Statistical Analysis -- Asteroid Belts and Spandex Cars: Using Descriptive Statistics to Answer Your Most Weighty Questions -- Baseball, Game Shows, and Sidekicks: Who Cares about Probability Anyway? -- What It's Like to Be Normal: Probability Distributions and One Rule That Could Make You Wildly Popular -- What a Few Estimates and a Little Probability Can Do for You. Men Are Insensitive and Women Are Illogical. Really: Asserting Your Stereotypes with Confidence -- Godzilla versus King Kong: How Hypothesis Tests Can Be Used to Settle the Battle of the Movie Monsters -- Lab Rats and Roommates: Analysis of Variance and How to Channel Your Inner Mad Scientist -- When the Zombie Flu Went Viral: Regressing the Myth Out of Urban Myths -- Appendix A: Critical Values for the Standard Normal Distribution -- Appendix B: Critical Values for the T-Distribution -- Appendix C: Critical Values for the Chi-Squared Distribution.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Mathematical statistics -- Popular works; Mathematical statistics -- Popular works; Mathematical statistics; Statistics; MATHEMATICS -- Probability & Statistics -- General; Mathematical statistics; Electronic books; Popular works; Electronic books